Percentage Refusal Density (PRD) Performance of Hot Rolled Sheet-Wearing Course (HRS-WC) Mixture with Substitution of Palm Shell Ash as Filler - Lusyana; mukhlis, Mukhlis; Enita Suardi; Era Alfansyuri; EtriSuhelmidawati; Rahmi Hidayati; Yan Partawijaya (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2025)
The increasing traffic volume and excessive loads on road pavements often cause permanent deformation in the wearing course layer. One potential solution is the utilization of industrial by-products, such as palm shell ash, as an alternative filler in Hot Rolled Sheet-Wearing Course (HRS-WC) mixtures. This study aims to evaluate the effect of palm shell ash substitution on the Optimum Asphalt Content (OAC) using the Marshall method and the Percentage Refusal Density (PRD) approach. The research was conducted through laboratory experiments with substitution variations of 0%, 25%, 50%, 75%, and 100%. The results indicate that the OAC determined by the Marshall method tends to increase with higher palm shell ash content, ranging from 7.46% to 8.30%. Meanwhile, the OAC values based on PRD range between 7.29% and 8.13%, with the 50% substitution producing the most optimal value at 7.29%. These findings suggest that palm shell ash has significant potential as an eco-friendly alternative filler to enhance the performance of HRS-WC mixtures while simultaneously promoting sustainable utilization of palm oil industry waste